PERSEPSI KEADILAN, PENGETAHUAN, DAN KOMPLEKSITAS PERPAJAKAN SEBAGAI DETERMINAN KEPATUHAN WAJIB PAJAK: STUDI EMPIRIS PADA KARYAWAN SWASTA - Dwi Martutik; Haris Ihsanil Huda; Vivi Kumalasari Subroto; Kasih Purwantini (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
Although national tax revenue realization has surpassed its target, the compliance level of Individual Taxpayers (WPOP) remains a crucial issue in Indonesia. This research is crucial because the rate of formal compliance with WPOP regulations is currently low, standing at 67.78% as of March 31, 2023 and preliminary findings of confusion and reporting delays within PT. Sunway Multi Kreasi. The purpose of this research was to examine how three factors – individuals’ perceptions of fairness, their understanding of tax laws, and the intricacy of the tax system – affect their adherence to tax regulations. The analysis was conducted partially and simultaneously on WPOP with private employee status at PT. Sunway Multi Kreasi. Adopting a quantitative explanatory design, this study collected primary data from 50 employees selected through purposive sampling. Data was gathered through a questionnaire. The collected data were then examined using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicated a positive and statistically significant relationship between perceived fairness (P=0.019) and tax compliance, as well as between tax knowledge and tax compliance (P=0.007). Between them, tax knowledge (β=0.416) emerged as the most dominant predictive factor. Conversely, the tax complexity variable (P=0.156) was found to have no significant impact. Concurrently, the three independent variables contributed to explaining 48.2% (R²=0.482) of the variability in tax compliance. The practical implication is that efforts to enhance compliance within a corporate environment should prioritize strengthening employees' technical competence. The non-significance of complexity indicates that the company's internal procedural support has likely succeeded in mitigating the negative impact of regulatory intricacies for employees